I'm trying to find the derivative of:

$$y= \frac{x \sin(x)}{1+\cos(x)}$$

I've tried but I can't achieve the simplified form -

Here's my try-

$$y' = \left(\frac{x \sin(x)}{1+\cos(x)}\right)'$$

$$y' = \frac{x\sin^2(x) + (\cos(x)+1 )(\sin(x)+x\cos(x))}{(\cos(x)+1)^2}$$

I'm pretty sure the above is correct that is why I didn't show the steps in between ... but I can't simplify it until -


Which concept or formula am I missing out from in order to simplify it further? Or what should I do next? Thanks!



$$\cos^2 x + \sin^2 x = 1$$

Therefore, the numerator becomes:

$$x\sin^2x + x\cos^2x + \sin x + \cos x \sin x + x\cos x$$

$$= x(\cos^2x + \sin^2x) +\sin(x)(\cos x + 1) + x \cos x$$

$$= x(1 + \cos x) + \sin x(\cos x + 1) $$

$$= (\cos x + 1)(x + \sin x)$$

Hence, the final result becomes:

$$y' = \frac{(\cos x + 1)(x + \sin x)}{(\cos x +1)^2} = \frac{x+\sin x}{1 + \cos x}$$

  • $\begingroup$ How did $sin(x) + cos x sin x$ became $sin(x)(cosx+1) $ $\endgroup$ – user307640 May 27 '17 at 14:27
  • $\begingroup$ factor out $\sin x$ using the rule $a + ba = a(1+b)$ $\endgroup$ – user370967 May 27 '17 at 14:30

Note that $x\sin^2 x = x(1 - \cos^2 x)$. So we can rewrite the numerator as $$x-x\cos^2 x + x\cos^2 x+(1+\cos x)\sin x +x\cos x = (1+\cos x)(x+\sin x)$$ so $$y'=\frac{(1+\cos x)(x+\sin x)}{(1+\cos x)(1+\cos x)} = \frac{x+\sin x}{1+\cos x}$$



Using Weierstrass Substitution, $\dfrac{\sin x}{1+\cos x}=\tan\dfrac x2$

$$\dfrac{d\left(\dfrac{x\sin x}{1+\cos x}\right)}{dx}=\tan\dfrac x2+\dfrac{x\sec^2\dfrac x2}2$$

Now $\dfrac{\sec^2\dfrac x2}2=\dfrac1{2\cos^2\dfrac x2}=\dfrac1{1+\cos x}$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.